PROSES BERPIKIR SISWA DALAM PEMECAHAN MASALAH MATEMATIKA PADA MATERI PERBANDINGAN DITINJAU DARI ADVERSITY QUOTIENT - Nuraini, Nuraini; Nursangaji, Asep; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to describe students thinking process in mathematical problem solving on proportion reviewed from adversity quotient. The research method used is descriptive and the form of research is case study. The subject of this research was students? of VIII B class which consist 33 students. Data collection tools used are proportion test and interview to reveal students thinking process, as well as questionnaires to classify students reviewed from adversity quotient. The results in this research shows that climber students thinking process, that is one students of conceptual thinking process, 13 students of semi conceptual thinking process, and 10 students of computasional thinking process. Camper students thinking process, that is one students of conceptual thinking process, four students of semi conceptual thinking process, and four students of computasional thinking process. While quitter students thinking process are not found in this research. Keywords : Process Thinking, Problem Solving, Proportion, Adversity Quoteint